Biphasic modulation of cAMP levels by the contraceptive nomegestrol acetate: impact on P-glycoprotein expression and activity in hepatic cells - Tocchetti, Guillermo Nicolás; Weiß, Johanna (Biochemical pharmacology, 2018)
ABC transporters are key players in drug excretion with alterations in their expression and activity by therapeutic agents potentially leading to drug-drug interactions. The interaction potential of nomegestrol acetate (NMGA), a synthetic progestogen increasingly used as oral contraceptive, had never been explored. In this work we evaluated (1) the effect of NMGA on ABC transporters in the human hepatic cell line HepG2 and (2) the underlying molecular mechanism. NMGA (5, 50 and 500nM) increased P-glycoprotein (P-gp) expression at both protein and mRNA levels and reduced intracellular calcein accumulation, indicating an increase also in transporter activity. This up-regulation of P-gp was corroborated in Huh7 cells and was independent of the classical progesterone receptor. Instead, using a siRNA-mediated silencing approach, we demonstrated the involvement of membrane progesterone receptor α. Moreover, we found that the activation of this receptor by NMGA led to a falling-rising profile in intracellular cAMP levels and protein kinase A activity over time, ultimately leading to transcriptional P-gp up-regulation. Finally, we identified inhibitory G protein and phosphodiesterases as mediators of this novel biphasic modulation. These results demonstrate the ability of NMGA to selectively up-regulate hepatic P-gp expression and activity and constitute the first report of ABC transporter modulation by membrane progesterone receptor α. If a similar regulation took place in vivo, decreased bioavailability and therapeutic efficacy of NMGA-coadministered P-gp substrates could be expected. This holds special importance considering long-term administration of NMGA and broad substrate specificity of P-gp.
Gesehen am 28.02.2020